2023
DOI: 10.1101/2023.03.03.531067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent Evolution of A-Lineage (Clade 19B) SARS-CoV-2 Spike Sequences with B-Lineage Variants of Concern Affects Virus Replication in a Temperature-Dependent Manner on Human Nasal Epithelial Cell Cultures

Abstract: The first three months of the COVID-19 pandemic was dominated by two SARS-CoV-2 lineages: A-lineages (Clade 19B) and B-lineages (Clade 19A). However, with the emergence of the Spike D614G substitution in B.1 lineages (Clade 20A), both early lineages were outcompeted and remained near-extinction from mid-2020 onwards. In early-2021, there was a re-emergence and persistence of novel A-lineage variants with substitutions in the Spike gene resembling those found in Variants of Concern (VOCs). An early A.3 variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 48 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Omicron replication, but have not been previously used to investigate variants derived from immunocompromised individuals [49], [50]. The physiological relevance of polarized hNEC cultures can reveal virus fitness differences not apparent on widely used immortalized cell line models [26], [30], [51], [52], [53]. On hNECs, there were no differences in total virus production between the Patient 2 virus isolates at 33°C, though some timepoints displayed slight differences across the isolates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Omicron replication, but have not been previously used to investigate variants derived from immunocompromised individuals [49], [50]. The physiological relevance of polarized hNEC cultures can reveal virus fitness differences not apparent on widely used immortalized cell line models [26], [30], [51], [52], [53]. On hNECs, there were no differences in total virus production between the Patient 2 virus isolates at 33°C, though some timepoints displayed slight differences across the isolates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown that physiological temperature ranges can alter influenza A virus and live attenuated influenza A virus replication kinetics on immortalized and primary cell cultures, and influenza B virus hemagglutinin protein expression is increased at cooler temperatures corresponding to the upper airway [51], [52], [53], [72], [73]. SARS-CoV-2 replication on hNECs is also variable at 33°C versus 37°C, and early A-lineage SARS-CoV-2 isolates show temperature-dependent differences in replication on both Vero/TMPRSS2 cells and hNECs [30], [74]. Comparisons using pseudoviruses bearing the SARS-CoV-2 Spike protein versus other human coronavirus Spikes using indicate that Spike is a key driver of coronavirus temperature preferences, and psuedovirus infectivity was heightened at 33°C in the case of SARS-CoV-2 but not SARS-CoV Spike [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations